Ciało w teatrze - między realnością a ﬁ kcją - Lilianna Dorak- Wojakowska (Jesuit University Ignatianum in Krakow, 2017)
This article is devoted to the relationship between an actor and a character. This relationship is a basic indicator of theatre whose material is the actor and speciﬁ cally his body. The body of an actor is his basic instrument which is characterised by a double existence which is clear to the viewer. It concerns a double life: two "personalities", two physical existences, awarenesses, memories and two times: the real and the ﬁ ctitious. Less obvious is the fact that an actor plays a double role at the same time, i.e. as signal material and co-author of the character who communicates with other characters in the ﬁ ctitious world, as well as an equally active element of playwrights' communication with the audience. That is why, one of the ways to describe the body in the theatre is the semiotics of the theatre, which is an analysis of a performance as a density of sign structure, referring to the space of the body and body techniques as a sign of signs. This article undertakes the problem of the representation of the body in the theatre. For, regardless of the kind of the theatre, the body is always interwoven with meanings. It takes place both in the traditional theatre, where the body is conventionalised, closed in deﬁ nite frameworks of form and convention and in para-theatrical events which abolish the basic opposition between an actor and a character performed by him. Pretending in theatre involves a signalised "recording" by an actor on his own body the perception of the world which belongs to the ﬁ ctitious character who perceives this world from a different time and space viewpoint.